2020
DOI: 10.1523/eneuro.0067-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic-Dependent miR-182 and QR2 Expression Regulation in the Anterior Insula Enables Novel Taste Learning

Abstract: Number of pages: 35 (including figures & legends, not including extended data) ⁘ Number of figures (5), tables (0), multimedia (0), and 3D models (0) (separately)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 61 publications
(68 reference statements)
4
37
0
Order By: Relevance
“…We have previously shown that miR-182 causes suppression of QR2 mRNA in the aIC (Gould et al, 2020). Since miR-182 is Figure 2.…”
Section: Novelty Of the Context Reduces Qr2 Expression Via Mir-182 Upregulationmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that miR-182 causes suppression of QR2 mRNA in the aIC (Gould et al, 2020). Since miR-182 is Figure 2.…”
Section: Novelty Of the Context Reduces Qr2 Expression Via Mir-182 Upregulationmentioning
confidence: 98%
“…Brains were stored at À80°C and then transferred to a cryostat (CM 1950, Leica Microsystems), whereupon they were equilibrated to À15°C. CA1 samples were removed from 0.5-mm-thick coronal slices (from bregma: AP À1.355 mm, to bregma: AP À2.48 mm) (Franklin and Paxinos, 2008) with the use of a tissue punching device, while control aIC samples were taken as previously described (Gould et al, 2020). For DAT Cre mice LC inactivation experiments, brains were removed and split with a coronal cut, separating the dorsal hippocampus and LC containing anterior and posterior parts of the brain.…”
Section: Brain Dissection and Tissue Preparationmentioning
confidence: 99%
See 3 more Smart Citations